Um elemento finito de tubo tridimensional para análise geometricamente não linear de dutos - Machado, Alexandre Cunha (2006)
In transport of fluids or even as structural elements, cylindrical shells are widely used in several segments of structure engineering. The understanding of the behavior of this type of structure along a trajectory of equilibrium resultant of a description of historical loading of different natures and, consequently, is important in the definition of the real load capacity of the ducts. In this work, a finite element for geometric and threedimensional nonlinear analyses of pipes is developed. Taking into account the nature of the analysis, proper measure of tension and deformation that are compatible with states of large deformations and displacements are studied. The Total Lagrangean formulation is adopted, but the constitutive relationships used are linear. The developed computational implementation uses a three-dimensional finite element of pipe with 2 or 3 nodes, compatible with the state of great deformations and displacements, and, also, incorporating the movements of rigid body of the structure.In order to map the nonlinear trajectories of equilibrium, using some methodologies proposed in the literature, a structure of Object-Oriented Programming is used. It allows the application of different techniques of incremental and iterative analysis integrated to the implementation of the aforementioned finite elements.Aiming to validate the formulation, the results obtained by using the program here developed are evaluated through their comparison with analytical solutions and previously published results.